Increasing Participation in Volunteer Computing - Toth, D.; Mayer, R.; Nichols, W. (2011 IEEE International Symposium on Parallel and Distributed Processing Workshops and Phd Forum, 2011)
Volunteer computing is a distributed computing model where a large problem requiring the computational power of a supercomputer can be solved by thousands or millions of personal computers. In volunteer computing, people allow their personal computers to work together on a large problem when the computers are not otherwise in use. The owners of the computers are not compensated for the use of their computers. As volunteer computing has become an accepted way to solve large problems, the number of volunteer computing projects has increased significantly over the years. However, as the number of volunteer computing projects increases, the participation in volunteer computing must increase to allow volunteer computing to remain a viable way to solve large problems. We studied the reasons that people do not participate in order to determine how participation can be increased. We found that the likelihood of people participating in such projects was not affected by how these projects were described. We also collected information about factors that influenced the subjects' decisions.